Identification and characterization of microRNAs in the pituitary of pubescent goats - Jing Ye; Zhiqiu Yao; Wenyu Si; Xiaoxiao Gao; Chen Yang; Ya Liu; Jianping Ding; Weiping Huang; Fugui Fang; Jie Zhou (BMC, 2018)
Abstract Background Puberty is the period during a female mammal's life when it enters estrus and ovulates for the first time; this indicates that a mammal is capable of reproduction. The onset of puberty is a complex and tightly coordinated biological event; it has been reported that microRNAs (miRNAs) are involved in regulating the initiation of puberty. Methods We performed miRNA sequencing on pituitary tissue from prepubescent and pubescent goats to investigate differences in miRNA expression during the onset of puberty in female goats. The target genes of these miRNAs were evaluated by GO enrichment and KEGG pathway analysis to identify critical pathways regulated by these miRNAs during puberty in goats. Finally, we selected four known miRNA and one novel miRNAs to evaluate expression patterns in two samples via qRT-PCR to validate the RNA-seq data. Results In this study, 476 miRNAs were detected in goat pituitary tissue; 13 of these were specifically expressed in the pituitary of prepubescent goats, and 17 were unique to the pituitary of pubescent goats. Additionally, 73 novel miRNAs were predicted in these two libraries. 20 differentially expressed miRNAs were identified in this study. KEGG pathway enrichment analysis revealed that the differentially expressed miRNA target genes were enriched in pathways related to ovary development during puberty, including the GABAergic synapse, oxytocin signaling pathway, the cAMP signaling pathway, progesterone-mediated oocyte maturation. In this study, differential miRNA expression in the pituitary tissue of prepubescent and pubescent goats were identified and characterized. Conclusion These results provide important information regarding the potential regulation of the onset of goat puberty by miRNAs, and contribute to the elucidation of miRNA regulated processes during maturation and reproduction.